МАТЕМАТИКА САБАҚЛАРЫНДА ОҚЫЎШЫЛАРДЫҢ ИЗЕРТЛЕЎ ИСЛЕРИ - Сапаров, З.; Жанабергенова, А. (FAN va JAMIYAT, 2017)
The article is devoted to the study of issues of the rational ways of thinking, proofs, performance of tasks and doing corresponding conclusions at the lessons in Mathematics.